Variations in eating habits between Ecuadorian parents and children related to excess weight - Natalia Romero Sandoval; Julieta Robles; María José Cisneros; Virginia Ruiz; Miguel Martín
Abstract Objectives: to evaluate the concordance of food consumption habits declared by parents and by their children, and relate it to excess weight prevalence. Methods: cross-sectional study. Concordance was analysed by Kappa and McNemar tests. The analysis of the discrepancies against excess weight was made by logistic regression. Results: we found high levels of discrepancy between parents and children: Kappa -0.02-0.31 (p≤0.01), McNemar p≤0.01. Excess weight did not vary in terms of the discrepancies, except for the affirmation of following a diet (ORadjusted: 1.79; CI95%: 1.49-2.14). Conclusions: agreement between parents and their children demonstrated discordance, but did not influenced on excess weight.